Chances to empower country’s logistics industry - Siti Nur Azwin, Zulkapri (2020)
Kuantan, 8 September 2020 - University students should take the opportunity to venture into the field of logistics and the use of digital platforms to empower the logistics industry in the country in line with Malaysia’s aspiration to become a major logistics hub in the Southeast Asian region.